2020
DOI: 10.3389/fmed.2020.00529
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Imaging With 18F-FDG- and 18F-Florbetaben-PET/MRI Detects Pathological Changes in the Brain of the Commonly Used 5XFAD Mouse Model of Alzheimer's Disease

Abstract: Imaging biomarkers of Alzheimer's disease (AD) that are able to detect molecular changes in vivo and transgenic animal models mimicking AD pathologies are essential for the evaluation of new therapeutic strategies. Positron-emission tomography (PET) using either 18 F-Fluorodeoxyglucose (18 F-FDG) or amyloid-tracers is a well-established, non-invasive tool in the clinical diagnostics of AD assessing two major pathological hallmarks. 18 F-FDG-PET is able to detect early changes in cerebral glucose metabolism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 66 publications
8
35
0
Order By: Relevance
“…Our [18F]-AV45 data are consistent with previous in vivo imaging studies in 5XFAD mice that looked at amyloid using a different tracer (18F-Florbetaben) and observed agedependent increases in amyloid (Jankowsky and Zheng, 2017;Franke et al, 2020). This study also observed alterations in brain glucose metabolism and amyloid deposition prior to the onset of behavioral changes (Franke et al, 2020). Although previous studies detected cerebral hypometabolism (Franke et al, 2020), the methods for quantification, ROI and ages of animals were different in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our [18F]-AV45 data are consistent with previous in vivo imaging studies in 5XFAD mice that looked at amyloid using a different tracer (18F-Florbetaben) and observed agedependent increases in amyloid (Jankowsky and Zheng, 2017;Franke et al, 2020). This study also observed alterations in brain glucose metabolism and amyloid deposition prior to the onset of behavioral changes (Franke et al, 2020). Although previous studies detected cerebral hypometabolism (Franke et al, 2020), the methods for quantification, ROI and ages of animals were different in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, PET using [18F]-FDG and PET with [18F]-AV45 revealed significant uptake at all ages in both male and female mice (Figures 6, 7), demonstrating that [18F]-AV45 PET/MRI is feasible for quantifying Aβ in this model but should be confirmed with additional methods (Jankowsky and Zheng, 2017). Our [18F]-AV45 data are consistent with previous in vivo imaging studies in 5XFAD mice that looked at amyloid using a different tracer (18F-Florbetaben) and observed agedependent increases in amyloid (Jankowsky and Zheng, 2017;Franke et al, 2020). This study also observed alterations in brain glucose metabolism and amyloid deposition prior to the onset of behavioral changes (Franke et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations